The Use of the Raabe Aspirator in Intraoperative neurophysiological Monitoring during Decompression and Stabilization Interventions for Degenerative Diseases and Injuries of the Lumbar Spine - N. A. Bobriakov (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. Raabe probe is a suction device with monopolar motor fibers mapping capabilities. A number of technical characteristics make it possible to use it for intraoperative neurophysiological monitoring during posterior lumbar fusion surgery.The aim of this study was to analyze our experience of Raabe probe using for intraoperative neurophysiological monitoring during posterior lumbar fusion surgery.Methods. Ninety-eight patients (55 women and 43 men) with degenerative changes and injuries of the lumbar spine were included into the study, mean age – 56.3 ± 12.8 years. Patients underwent the following operations: 85 cases (86.7 %) – spinal roots decompression with fusion by dorsal and ventral implants, 12 cases (12.2 %) – decompression with only dorsal fusion, 1 case (1.0 %) – dorsal fusion without decompression. In all cases intraoperative neurophysiological monitoring control by B. Calancie method with Raabe probe using was performed.Results. With a critical current threshold of 12 mA, the sensitivity of the method is 94 %, the specificity is 97 %. Comparing the thresholds of the M-response at the stage of screw stimulation, no statistically significant differences were found between the groups of true-positive and false-positive results, both for interested (p = 0.09) and intact (p = 0,16) screws. At the stage of the impactor stimulation, the threshold of the M-response in the true-positive group made11.39 ± 7.97 mA, and in the false-positive group – 24.16 ± 8.85 mA (p < 0.05).Conclusion. Raabe probe application for intraoperative neurophysiological monitoring during posterior lumbar fusion surgery show the high sensitivity and specificity. The most reliable sign of pedicle wall breach is a threshold below than 12 mA at the stage of the impactor stimulation.